Impact of Future Remnant Liver Volume on Post-Hepatectomy Regeneration in Non-Cirrhotic Livers - Pagano, Duilio; Gruttadauria, Salvatore (Frontiers in Surgery, 2014)
Objective: The purpose of the study is to detect if some parameters can be considered as predictors of liver regeneration in two different patient populations composed of in living donors for adult to adult living donor liver transplant and patients with hepatic malignancies within a single institution. Summary Background Data: Preoperative multi-detector computed tomography volumetry is an essential tool to assess the volume of the remnant liver. Methods: a retrospective analysis from an ongoing clinical study on 100 liver resections, between 2004 and 2010. 70 patients were right lobe living donors for liver transplantation and 30 patients were resected for treatment of tumors. Pre-surgical factors such as age, weight, height, body mass index (BMI), original liver volume, future remnant liver volume (FRLV), spleen volume, liver function tests, creatinine, platelet count, steatosis, portal vein embolization (PVE) and number of resected segments were analyzed to evidence potential markers for liver regeneration. Results: Follow-up period did not influence the amount of liver regenerated: the linear regression evidenced that there is no correlation between percentage of liver regeneration and time of follow-up (p=0.88). The pre-surgical variables that resulted markers of liver regeneration include higher preoperative values of BMI (p=0.01), bilirubin(p=0.04), glucose (p=0.05) and GGT (p=0.014); the most important association was revealed regarding the lower FRLV (p< 0.0001) and percentage of liver regeneration. The stepwise regression revealed a strong impact of FRLV (p< 0.0001) on the other predictor variables. Conclusions: Liver regeneration follows similar pathway in living donor and in patients resected for cancer. Small FRLV tends to regenerate more and faster, confirming that a larger resections may lead to a greater promotion of liver regeneration in patients with optimal conditions in terms of body habitus, preoperative liver function tests and glucose level.